2023
DOI: 10.1002/cpp.2826
|View full text |Cite
|
Sign up to set email alerts
|

The role of metacognitions in cyberbullying and cybervictimization among adolescents diagnosed with major depressive disorder and anxiety disorders: A case–control study

Abstract: Cyberbullying is becoming increasingly widespread as individuals use technology more widely and frequently. Recent studies have shown a growing vulnerability for cyberbullying and cybervictimization, particularly in the adolescent population. We argue that dysfunctional metacognitions, which have been found to be prominent in various psychiatric disorders, may also play a role in predicting cyberbullying and cybervictimization over and above a variety of established factors including daily Internet use, social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Cyberbullying may cause women to feel helpless, ashamed, or unable to advance in their careers (Tang et al, 2023). Ünal-Aydın et al (2023) observed that adolescents with anxiety disorders may have defective metacognitions, which can play a role in predicting cyberbullying and cybervictimization. Yosep et al (2023) argued that e-parenting may be an efficient solution in the fight against the damage done by cyberbullying to students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cyberbullying may cause women to feel helpless, ashamed, or unable to advance in their careers (Tang et al, 2023). Ünal-Aydın et al (2023) observed that adolescents with anxiety disorders may have defective metacognitions, which can play a role in predicting cyberbullying and cybervictimization. Yosep et al (2023) argued that e-parenting may be an efficient solution in the fight against the damage done by cyberbullying to students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both cyberbullying and social media addiction have been associated with psychological distress [ 25 ]. A study among Bosnian adolescents in a state hospital showed that those diagnosed with anxiety and depressive disorders had higher scores for cybervictimization [ 26 ]. Another study among 1691 Malaysian adolescents revealed that both before and during the COVID-19 pandemic, those with depression symptoms had a higher tendency to experience cyberbullying [ 27 ].…”
Section: Introductionmentioning
confidence: 99%